If it's not what You are looking for type in the equation solver your own equation and let us solve it.
D( x )
x-1 = 0
x-1 = 0
x-1 = 0
x-1 = 0 // + 1
x = 1
x in (-oo:1) U (1:+oo)
x-(10/(x-1)) = 4 // - 4
x-(10/(x-1))-4 = 0
x-10*(x-1)^-1-4 = 0
x-10/(x-1)-4 = 0
(x*(x-1))/(x-1)-10/(x-1)+(-4*(x-1))/(x-1) = 0
x*(x-1)-4*(x-1)-10 = 0
x^2-x-4*x-10+4 = 0
x^2-5*x-6 = 0
x^2-5*x-6 = 0
x^2-5*x-6 = 0
DELTA = (-5)^2-(-6*1*4)
DELTA = 49
DELTA > 0
x = (49^(1/2)+5)/(1*2) or x = (5-49^(1/2))/(1*2)
x = 6 or x = -1
(x+1)*(x-6) = 0
((x+1)*(x-6))/(x-1) = 0
((x+1)*(x-6))/(x-1) = 0 // * x-1
(x+1)*(x-6) = 0
( x+1 )
x+1 = 0 // - 1
x = -1
( x-6 )
x-6 = 0 // + 6
x = 6
x in { -1, 6 }
| -3x^2+4=4x | | -7n-n=-24 | | x+x=30-10 | | 5+3q-4=2q+1 | | x-10/(x-1)=0 | | (t-7)(t-7)=(t+7)(t+7)+168 | | x-(10/(x-1))=0 | | 4+6(6x-1)=-5(-x+5)-8 | | 9x-12-2x=11x+6 | | 11-9x-7-6x=7 | | (x-2)+2(x-2)-24=0 | | -2p-6p=-24 | | 7=8x-4 | | (4x^2+16x+16)(x-2)=x^2-4 | | 2x^4-7x^2+2=0 | | 2t-3=3(t-4) | | 2-0.6k=2 | | 36=3(4-x) | | 5x+x=8x+55+9x | | 25x-3=35x+5 | | 2p^3*6p^4= | | 20*.15= | | 8y-7-6y+2=0 | | 3x+27=20x-43 | | x/9+4=13 | | -9(x-4)+5x=-4(x+8)+5 | | 9*19+9= | | 2(4x+9)=-42+36 | | -x^2+8x-52=0 | | 12=4r-8+6r | | 4x-1(60-x)=130 | | 12/3x2/8 |